2005
DOI: 10.2741/1598
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic hydrolysis of luminal coronary glycosidic structures uncovers their role in sensing coronary flow

Abstract: Endothelial luminal glycocalyx (ELG) is a multifunctional complex structure made off of a diversity of glycosilated proteins, and glycosaminoglycans (GAG). Coronary ELG may participate as a sensor of coronary flow (CF) to induce inotropic and dromotropic effects. In isolated perfused guinea pig heart we tested the role of glycosidic groups of glycans bound to proteins and GAG of the ELG on CF-induced inotropic and dromotropic effects. To study the role of saccharide related groups of certain glycans, they were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Work from our laboratory and many others have shown that the perfusion of heparinase into blood vessels removes endothelial surface layer heparinic functional groups [10,11,31,13,39,40,42]. Heparinate, a branched oligosaccharide, is known to be lectinically bound to endothelial surface layer functional [40].…”
Section: Group 4: Effects Of Heparinase On the Concentration-vascularmentioning
confidence: 99%
See 4 more Smart Citations
“…Work from our laboratory and many others have shown that the perfusion of heparinase into blood vessels removes endothelial surface layer heparinic functional groups [10,11,31,13,39,40,42]. Heparinate, a branched oligosaccharide, is known to be lectinically bound to endothelial surface layer functional [40].…”
Section: Group 4: Effects Of Heparinase On the Concentration-vascularmentioning
confidence: 99%
“…To minimize the possibility of transendothelial diffusion, heparinase was administered repeatedly using a low concentration gradient and very short exposure times [8,11,13,31,44]. As described above, control concentration-response curves to bradykinin were obtained at 11 ml/ min (basal pressure 52.4 ± 2.6 mmHg) and at 16 ml/min (basal pressure 81.2 ± 6.8 mmHg).…”
Section: Groupmentioning
confidence: 99%
See 3 more Smart Citations